Globalisation and productivity growth : (Palgrave MacMillan, 2005)
It has long been acknowledged that productivity growth is key to rising living standards and poverty reduction. This book comprises a coherent collection of studies of links between globalization and productivity growth. Chapters cover all aspects of firm entry to international markets including foreign direct investment, acquisition and arms length exports.